Fundos de investimento: estrutura jurídica e agentes de mercado como proteção do investimento privado - Pavia, Eduardo Cherez (2015)
This is a master s dissertation which aims to make a contribution to the analysis under the legal aspect of the operation of the investment fund industry in Brazil and the agents who participate in it. Accordingly, we shall analyze the historical remote precedents and the development of the structures of collective investment schemes in the world, the history of invesment funds in Brazil, as well as the financial and capital markets regulation nowadays, the regulators and the legal nature of investment funds. Also, we shall decribe the roles of each participant agent of the industry and the rules and regulation which they are submitted to. Finally, the liability of the administrator and the investment manager, essential players of investment funds, will be outlined. The purpose will be to try to conclude that the existing legal and regulatory framework, as well as self-regulation and court decisions, work as a network for investor protection and private investments